Transformasi Kepemimpinan Adaptif: Kolaborasi Gaya Situasional, Transformasional Dalam Tata Kelola Universitas Linggabuana PGRI Sukabumi - Lina Herlina; Akhyar Fauzi; Ginanjar Theonata; Erry Sunarya (DIALEKTIKA: Jurnal Ekonomi dan Ilmu Sosial, 2026)
The emergence of the digital age and global uncertainty has compelled firms to implement strategy modifications, necessitating adaptable and transformative leadership. This essay examines leadership dynamics in the context of situational change and uncertainty through a descriptive-qualitative methodology. It emphasizes leaders' competencies in managing organizations and teams amid uncertainty, highlighting the significance of situational and transformational leadership theories. The study illustrates instances of disruptive change inside businesses and delineates the attributes of contemporary leaders: analytical acumen for thorough assessment and communication proficiency for fostering trust and facilitating successful collaboration. Case studies illustrate team dynamics under strain and the strategic decision-making of leaders. The essay examines the progression of leadership in the digital age, incorporating information technology. The results underscore that contemporary leaders must comprehend classical theories, adapt to technological advancements, and remain attuned to global socio-economic dynamics to enhance leadership theory and practice.